Development of Higher Order Thinking Skills (HOTS) Measurement Ability Instruments in Learning High School Biology - Iqlas Sari AS; Ade Dewi Maharani; Yosmed Hidayat (Ta'dib, 2021)
This study aims to produce instruments that can measure the level of students' higher order thinking skills that are valid and practical for students of class XI SMA. The developed instrument contains 40 multiple choice questions, and 10 essay questions consisting Taxonomy Levels C4, C5, and C6 with indicators of high-level thinking critical thinking, decision making, problem solving and creative thinking. This  research used the Research and Development (R&D) type of Tessmer's modified formative evaluation with the stages of self-evaluation, prototyping (expert review, one-to-one, and small group). The result of tis research indicates that the instrument for measuring higher order thinking skills in class XI Biology SMA students developed is categorized as very valid and very practical with the validity value of expert rivew very valid (89.9%), one-to-one is very valid (87, 5%)). And the practical value of teachers is very practical (91.33%), and students are very practical (87.15%).